1966
DOI: 10.1530/jrf.0.0110145
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intra-Uterine Spirals and Hormones on the Uterine Histology of the Ovariectomized Goat

Abstract: Studies on the mechanism of action on intra-uterine foreign bodies are gaining importance in the field of reproductive biology. Doyle & Margolis (1963, 1964a, b) found in the rat that, following ovulation and fertilization, implantation did not occur in the threaded uterine horn due to a hostile uterine environment and interference with the normal decidual reaction. Buch, Shukla & Hawk (1964) showed that in the Surti water buffalo an intra-uterine polyethylene loop prevented ovulation. In cows, Hawk, Conley,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1968
1968
1985
1985

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The presence of an IUD in one horn of the uterus in rats (Parr & Segal, 1966;Parr, 1969;Saksena, Lau & Castracane, 1974), rabbits (Ledger & Bickley, 1966), hamsters (Saksena et al, 1974), and goats (Janakiraman, Shukla, Gadgil & Buch, 1966) has been shown to cause an increase in the weight ofthat horn when compared with that of the control horn. It has been suggested that such an increase in weight and uniform growth is due to chronic inflammation even though administration of hydrocortisone failed to suppress such a response (Parr & Segal, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of an IUD in one horn of the uterus in rats (Parr & Segal, 1966;Parr, 1969;Saksena, Lau & Castracane, 1974), rabbits (Ledger & Bickley, 1966), hamsters (Saksena et al, 1974), and goats (Janakiraman, Shukla, Gadgil & Buch, 1966) has been shown to cause an increase in the weight ofthat horn when compared with that of the control horn. It has been suggested that such an increase in weight and uniform growth is due to chronic inflammation even though administration of hydrocortisone failed to suppress such a response (Parr & Segal, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…An IUD in one horn of the uterus in rats (Parr & Segal, 1966), rabbits (Ledger & Bickley, 1966) and goats (Janakiraman, Shykla, Gadgil & Buch, 1966) caused an increase in the weight of that horn when compared to the control horn. An IUD probably also increased the weight of the human uterus (Dickin¬ son & Smith, 1913; Grafenberg, 1931;Israel & Davis, 1966).…”
Section: Introductionmentioning
confidence: 99%